Complete Nucleotide Sequence of Plasmids of Two Escherichia coli Strains Carrying blaNDM–5 and blaNDM–5 and blaOXA–181 From the Same Patient - Marchetti, Vittoria Mattioni; Bitar, Ibrahim; Mercato, Alessandra; Nucleo, Elisabetta; Bonomini, Annalisa; Pedroni, Palmino; Hrabak, Jaroslav; Migliavacca, Roberta (Frontiers in Microbiology, 2020)
Aim of this study was to genetically characterize two carbapenemase-producing Escherichia coli strains obtained from a pediatric patient affected by diarrhea, expressing OXA-181 and/or NDM-5 type enzymes. The above microorganisms were collected in the same Desenzano hospital (Northern Italy) where the blaNDM-5 gene was detected for the first time in Italy three years ago. One strain (5P), belonged to sequence type ST405/ST477 (according to Pasture/Oxford schemes) and serotype O102:H6. It was characterized by a 130562bp multi-replicon plasmid IncFII/IncFIA/IncFIB (pVSI_NDM-5) enclosing two main antibiotic resistance islands: i) ARI-I, 10030bp in size, carried genes coding for β-lactam- (blaOXA-1, blaCTX-M-15), fluoroquinolone/aminoglycoside- (aac(6’)-lb-cr) and phenicol- resistance (catB3), ii) ARI-II, 15326 bp in size, carried genes coding for sulphonamide- (sul1), β-lactam- (blaNDM-5, blaTEM-1B), phenicol- (catB3), trimethoprim- (dfrA17), antiseptic- (qacEΔ1) and aminoglycoside- (aadA5, rmtB) resistance. The other isolate (5M), belonged to sequence type ST2659/ST759 and serotype O50/02:H18, and carried four plasmids: a 153866bp multi-replicon IncFII/IncFIA/IncFIB (pISV_IncFII_NDM-5), an 89866bp IncI1 plasmid, a 51480bp IncX3 plasmid (pISV_IncX3_OXA181), and a 41143bp IncI plasmid (pISV_IncI_CMY-42). pISV_IncFII_NDM-5 carried two main antibiotic resistance islands: i) ARI-III, 12220bp in size, carried genes coding for β-lactam- (blaOXA-1), fluoroquinolone/aminoglycoside- (aac(6’)-lb-cr), tetracycline- (tet(B)) and phenicol- resistance (catB3,catA1), and ii) ARI-IV, 26527bp in size, carried determinants coding for macrolide- (erm(B), mph(A)), sulphonamide- (sul1), beta-lactam- (blaNDM-5, blaTEM-1B), trimethoprim- (dfrA14, dfrA12), antiseptic- (qacEΔ1) and aminoglycoside- resistance (aadA5). pISV_IncI_CMY-42 harboured the blaCMY-42 gene coding for beta-lactam resistance, pISV_IncX3_OXA181 harboured genes encoding fluoroquinolone- (qnrS1) and beta-lactams- resistance (blaOXA-181). In conclusion, the detection of two different NDM-5 E. coli strains from a pediatric patient with a history of travel to the Far East countries strongly highlight an increasing trend and risk of importation from such areas.